Heritage amid an urban crisis: Historic preservation in Cleveland, Ohio's Slavic Village neighborhood. (October 2016) - Ryberg-Webster, Stephanie
Abstract: Cleveland, Ohio's Slavic Village is a shrinking neighborhood within a shrinking city that, in recent years, garnered national attention as an epicenter of the foreclosure crisis. High vacancy rates, deferred maintenance, vandalism, and low market-values present challenges to neighborhood leaders and policymakers. While demolition has dominated policy discourses in shrinking cities, Slavic Village's built environment is the tangible manifestation of the community's rich working-class and immigrant heritage. Thus, this research asks: In an era of urban shrinkage, what role do heritage and historic preservation play in stabilizing or revitalizing shrinking neighborhoods? Drawing on a qualitative case study of Slavic Village, the findings show that neighborhood leaders value heritage, yet historic fabric is in peril as traditional preservation regulations and incentives are insufficient given the scale of devastation. For historic preservation to retain relevance in places like Slavic Village, the profession needs to consider new, creative, even radical approaches that respond to the challenges of urban shrinkage. Highlights: Community developers and others value heritage and promote it as an asset. Traditional preservation regulations and incentives fail in weak-market contexts. Preservation policies and programs need to be updated in response to shrinkage. Urban shrinkage provides an opportunity for creative and experimental preservation.